Final Report to DETYA on the GrassGro Teaching Project. - Scott J. M.; Daily, H. G.; Hinch, G. N. ([Committee for University Teaching and Staff Development (CUTSD)], 2001)
This is a final report for a 1999 National Teaching Development Grant funded by the Committee for University Teaching and Staff Development. The report details the key achievements of the project and justifies the selection of GrassGro software as a teaching/learning tool. The evaluation of the project is supported by graphics and tables.